Peer Tutoring for Anatomy Workshops in Cambodia. Issue 1 (31st July 2018) - Pickles, Kylie; Ivanusic, Jason J.; Xiao, Junhua; Durward, Callum; Ryan, Andrea B.; Hayes, Jennifer A.
Abstract : Historical loss of staff and teaching resources in Cambodia has resulted in significant challenges to anatomy education. Small group anatomy teaching opportunities are limited. A visit to Cambodia by a teaching team from the University of Melbourne in 2010 demonstrated it was possible to implement well‐resourced anatomy workshops for this purpose. However, continuation of the workshop program was inhibited by the limited number of local teaching staff. In 2015, another team from the University of Melbourne returned to Cambodia to implement anatomy workshops that incorporated peer tutoring. The objective was to improve teacher‐to‐student ratios and to demonstrate that interactive anatomy workshops could be delivered successfully despite low staff numbers. The anatomy workshops were attended by 404 students of Medicine, Dentistry, Nursing, and Midwifery at the University of Puthisastra. Medical students were invited to act as peer tutors for nursing students. A five‐point Likert scale questionnaire was used to determine student satisfaction with both the workshops and peer tutoring. The overwhelming majority were positive about the workshops and keen for them to continue . Almost all medical students who acted as peer tutors agreed or strongly agreed that this role increased their anatomical knowledge (98%) and confidence (94%). Most nursing students agreed or strongly agreed with statements that they would like peer tutoring to continue (94%) and that they would like to be peer tutors themselves (88%). This report demonstrates that peer tutoring could be an effective tool in educational settings where poor staff‐to‐student ratios limit delivery of interactive workshops.